ITERS-R as a tool for improving quality in Norwegian ECEC settings: A critical reflection - Karen Marie Eid Kaarby; Cato Tandberg (European Teacher Education Network, 2018)
This study shows and discusses how the use of Infant/Toddler Environment Rating Scale-Revised (ITERS-R) can contribute to the development of pedagogical content knowledge (PCK) in physical active play and science for early childhood teachers. These items are described in ITERS-R, and a full-ended scoring procedure and results on each item-indicator yielded a nuanced picture based on 206 Norwegian kindergartens. Some of the indicators were close to cultural values, while other indicators revealed a missing awareness of PCK. We suggest that ITERS-R reveals a framework for possible quality, and that teachers need an increased awareness of PCK.